Weak cell cycle dependency but strong distortive effects of transfection with Lipofectamine 2000 in near‐physiologically synchronized cell culture. Issue 4 (12th October 2016) - Fuge, Grischa; Zeng, An‐Ping; Jandt, Uwe
Abstract : Previously, we reported a method to generate and validate cell cycle‐synchronized cultures of multiple mammalian suspension cell lines under near‐physiological conditions. This method was applied to elucidate the putative interdependencies of the cell cycle and recombinant protein expression in the human producer cell line HEK293s using Lipofectamine 2000 and the reporter plasmid pcDNA3.3 enhanced green fluorescent protein, destabilized using PEST sequence. A population‐resolved modeling approach was applied to quantitatively assess putative variations of cell cycle dependent expression rates based on the obtained experimental data. We could not confirm results published earlier by other groups, based on nonphysiological synchronization attempts, reporting transfection efficiency being strongly dependent on the cell cycle phase at transfection time point. On the other hand, it is demonstrated that transfection and protein expression distort the progression of the cell cycle.